Positive Education in the EFL Classroom: Observations and Ideas - Mandić, Maja M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The aim of this paper is to discuss the main principles of Positive Education, an approach to learning and teaching based on the ideas of positive psychology, which combines traditional education with the study of well-being and happiness. According to this approach, the skills for increasing well-being can and should be taught in school because they help students learn better and achieve higher academic success (Adler, 2016; Durlak et al., 2011; Fredrickson, 2004; 2005; Hoare et al., 2017; Seligman, 2008; 2017; Seligman & Adler, 2018; Seligman et al., 2009). The paper describes and discusses EFL classes based on Positive Education, implemented as part of two elective EFL courses at a university. The paper uses the principles of Exploratory Action Research (Smith & Rebolledo, 2018; 2022) to examine the effects of applying materials and practices grounded in Positive Education, as observed in students’ responses and classroom dynamics. The classes were aimed at combining teaching traditional foreign language skills (e.g., listening, speaking, and writing) with well-being skills (e.g., raising self-awareness, social awareness, and empathy) (Durlak et al., 2011; Norrish et al., 2013; Rimm-Kaufman et al., 2014; Seligman, 2008). Positive and negative aspects of the classes are discussed in order to understand their potential in working with new student groups. The paper provides suggestions for future work with university students.
Keywords: Positive Education; EFL; Exploratory Action Research; self-awareness; social awareness; empathy